Issues and potential of mosque as a spiritual tourism destination in Malaysia - Abdul Aziz, Maimunah; Ibrahim, Mansor; Jahn Kassim, Puteri Shireen; Abdullah, Alias (World Research Library, 2016)
Spiritual tourism is a new discovery area in the field of Religious Tourism, for example Islamic Tourism. The emergence and development of Islamic Tourism has encouraged people to travel to Islamic countries for many reasons, including educational, religion and spirituality purposes. Some people are travelling for spirituality of a place, but some are looking for educational aspects of the place. In Malaysia, Islamic Tourism is drastically developing since the country has the various assets for Islamic destination to exhibit their religion and culture like mosque, university and museums. Being an Islamic country, one of dominant Islamic tourism destinations in Malaysia is the mosque. Mosque is a ‘concrete symbol’ and ‘cultural pride’ of the country as it portrays the Muslim society and nationhood in Malaysia. Besides, since the early days, mosque plays pivotal roles by serving a comprehensive function to the community including educational, cultural and political matters. Unfortunately, in the current scenario, it does not really function as it was before. Therefore, the paper intended to discover issues and potential of mosque as a tourism destination pride in Malaysia through document analysis and interview with the mosque officers. Through the issues identified, a structural research framework could be developed to maximize mosque’ role and function as a tourism destination in Malaysia. This writing is beneficial for the researchers as well as destination planners to develop research in discovering tourists’ needs and satisfaction on mosque’s condition and management in Malaysia, more specifically in Kuala Lumpur and Putrajaya.